Penambahan ekstrak buah Mengkudu (Morinda citrifolia) dalam air minum terhadap performa broiler - Merry Muspita Dyah Utami; Mareta Fitriana; Aryanti Candra Dewi (Jurnal Ilmu Peternakan Terapan, 2023)
Mengkudu fruit contains antioxidant substances to increase endurance, increase appetite, and reduce fat. This study aims to determine the effect of using noni fruit extract (Morinda Citrifolia) to improve broiler performance. The study used a completely randomized design (CRD) with 4 treatments and 4 replicates of 5 birds each. Treatments based on the concentration of mengkudu extract (EM) consisted of P0: control, P1: 10% EM, P2 12.5% EM, and P3: 15% EM. The treatment was given when the DOC was 1 day old until 28 days old. The research parameters were feed consumption, body weight gain, and feed conversion. The results showed that the use of noni extract in drinking water had no effect on broiler performance, body weight gain, and feed conversion. The use of mengkudu extract in drinking water from the level of 10 to 15% decreased feed consumption, increased body weight gain, and decreased broiler feed conversion significantly compared to the control. The addition of mengkudu extract in drinking water up to 15% improved broiler performance.